Covid-19 and higher education institutions: addressing sustainable university agenda through university community engagement - Abdullah, Muhammad Faris; Hashim, Khairusy Syakirin Has-Yun; M. Yusri, Nurain Zahira (Zes Rokman Resources, 2020)
Operationally, sustainable university must involve three main activities which are administration, education, and research. It must also consider the engagement with local community. University usually uses the medium of outreach programmes to extend sustainability concept towards the local community. However, the concept of University Community Engagement (UCE) can be challenging especially during this Covid-19 pandemic. Covid-19 gives both positive and negative impacts towards UCE. Global report shows that the effect of Covid-19 on UCE was mainly negative for Asia & Pacific region. Nevertheless, the report only represents the members of the International Associations of Universities (IAU). How about other universities that are not involved in the report? Has their community engagement affected by this pandemic? As one of the universities that are not included in the IAU report, International Islamic University Malaysia (IIUM) can be a good case study. Therefore, this study aims to analyse the impact of Covid-19 towards IIUM’s community engagement during and after the pandemic. IIUM has taken progressive approach by inculcating maqasid shariah to drive its agenda towards the sustainability of the university. This paper first look at UCE undertaken by IIUM during the Covid-19 pandemic. It then discusses the relationship of maqasid shariah to UCE. The collected data on IIUM’s UCE projects were analysed using matrices to identify relationships to maqasid shariah. This paper concludes with recommendations on linking maqasid shariah to UCE post-Covid-19 period. This study oversees how maqasid shariah helps in justifying the needs of community engagement programmes conducted by IIUM and may contribute additional insights to the body of knowledge of UCE literature.